Inhibitory effect of Yukmijihwang-tang, a traditional herbal formula against testosterone-induced benign prostatic hyperplasia in rats - Shin In; Lee Mee; Ha Hye; Seo Chang; Shin Hyeun-Kyoo (BMC, 2012)
Abstract Background Yukmijihwang-tang, a traditional herbal formula, has been used for treating disorder, diabetic mellitus and neurosis in China (Liu-wei-di-huang-tang in Chinese), Japan (Lokumijio-to in Japanese) and Korea for many years. In this study, we investigated the effects of Yukmijihwang-tang water extract (YJT) on the development of benign prostatic hyperplasia (BPH) using a rat model of testosterone propionate (TP)-induced BPH. Methods A total of 30 rats were divided into five groups. One group was used as a control and the other groups received subcutaneous injections of TP for 4 weeks to induce BPH. YJT (200 or 400 mg/kg) was administered daily for 4 weeks to two groups by oral gavage concurrently with the TP. The animals were euthanized, the prostate and body weights were recorded, and tissues were subjected to hormone assays and histomorphology. In addition, we investigated proliferating cell nuclear antigen (PCNA) expression in the prostate using immunoblotting. Results Animals with BPH showed significantly increased absolute and relative prostate weights, increased dihydrotestosterone levels in the serum or prostate and increased PCNA expression in the prostate; however, YJT-treated animals showed significant reductions compared with the animals with TP-induced BPH. Histomorphology also showed that YJT inhibited TP-induced prostatic hyperplasia. Conclusions These findings indicate that YJT effectively inhibited the development of BPH and might be a useful drug clinically.